An investigation of the JEFF 3.2 nuclear data library. (April 2022) - Glinatsis, Georgios; Carta, Mario; Gugiu, Daniela; Ikonomopoulos, Andreas; Visan, Iuliana
Highlights: Study carried out on taking confidence on using the cross-sections data. Sub-critical (MOX/Pb) and Critical (Carbide/Na) core designs have been studied. Integral neutron parameters and reactivity coefficients behave as expected. Confidence, reliability and intrinsic consistency of the results have been observed. It seems reasonable to extend the above conclusion to similar nuclear systems. Abstract: In order to take confidence on using the JEFF 3.2 nuclear data library, an investigation of the integral neutronic parameters (the multiplication factor as a function of the fuel temperature and the whole core temperature, while keeping constant the geometry and atomic densities) has been performed for two different fast systems: a sub-critical oxide-fuelled/Pb-cooled core and a critical carbide-fuelled/Na-cooled core, respectively. Notwithstanding a small deviation of the cross section data at 800 K (more evident in case of the sub-critical MOX-fuelled/Pb-cooled reactor), the results obtained exhibit an expected behaviour. The analyses of the results show the complexity of the problem, including a multitude of physical phenomena due to many nuclear interactions in the reactor core. Sensitivity analysis would provide detailed information, while the involvement of the processing code should not be excluded.